ChemInform Abstract: Efficient New Synthesis of N‐Arylbenzo[b]furo[3, 2‐d]pyrimidin‐4‐amines and Their Benzo[b]thieno[3, 2‐d]pyrimidin‐4‐amine Analogues via a Microwave‐Assisted Dimroth Rearrangement. Issue 7 (18th February 2014) - Loidreau, Yvonnick; Dubouilh‐Benard, Carole; Marchand, Pascal; Nourrisson, Marie‐Renee; Duflos, Muriel; Buquet, Catherine; Corbiere, Cecile; Besson, Thierry
Abstract Compounds (V) and 20 compounds of type (VII) are prepared which are tested for their antiproliferative effects.